Revising Bilateral Investment Treaties as a New Tendency in Foreign Investment Law: India and Indonesia in the Focus - Pejovic, Caslav; Pardede, Juliartha Nugrahaeny (Indonesian Journal of International Law, 2020)
In the second half of 20th century the central theme of foreign investment debates was on balancing conflicting interests between developed and developing countries. As one of the most visible signs of this tendency is the process of revising bilateral investment treaties (BITs). This paper has focus on two countries, India and Indonesia. These two countries have been selected not only because of their size and importance for foreign investors, but also because of important reforms regarding BITs undertaken by these two countries that have attracted worldwide attention, particularly in other developing countries. These two countries have taken different routes, but motivated by similar concerns and objectives, and represent some of the most striking examples of the new tendency towards revision of BITs. The key issue that will be explored in this text is: What can be expected from this process of revising BITs and do the new BITs model provide for a good balance between the interests of host states and foreign investors? This is the core issue of foreign investment law, from the perspective of developing countries, which raises several further questions: How to design foreign investment law so that foreign investment can be attracted without impairing the interests of the host states? Is that possible at all, and what would be the good balance that developing countries should aim at? And, the central issue of this paper is: Do new BITs models contribute to these objectives of developing countries?